A Língua Inglesa na mídia publicitária de um instituto de idiomas e suas relações dialógicas com o discurso, a identidade e a ideologia na contemporaneidade - Wolf, Fábio (2014)
ThisresearchaimstodiscusshowEnglishisstructured in aninstituteoflanguagesadvertisingand its dialogicalrelationswiththediscourse, identity, andideology in thepresentdays. The presenceofEnglish in advertisementisnotableand does impress, mostly in thelastdecade. Continuously, social subjects are exposedtoseveralconstituentssymbolicsphereofadvertisingmaterials: billboards, brochures, posters, flyers, signs, televisioncommercials, jingles, etc. Linguisticdiscursiveinterrelationsbetweentheadvertisingsphereandthesubjectswhointeractwith it, or are inserted in it, basedonthehypothesisthatwillbediscussed in thisthesis, are anchored in conflictingdialogicalrelations. In thiscontext, identityandideologicalissues are stood out according as theypromote, throughthediscursive bias, the dialogue with speakers andinterlocutors in conflicting networks, makingevaluativepositionsconcerningthehegemonic status whichEnglishhasbeenenjoying in recent times, andhowthislanguageisconstructedandoperatedby its members. Thisinterrelationshipiswovenbytheintercrossofvoices, theconfrontationwithothers, coupledtothediscursivememory. The interspeechisconstitutedmultiplyandheterogeneouslywhichsupportsthisentireplot (CORACINI, 2003). In ordertodiscusstheimplicationsoflanguageandideology, thisworkwasbasedon BAKHTIN Circle stheoryofdialogicaldiscourse (2003, 2009, 2010). From colonial periodtothepresentdays, thesocio-historical status ofEnglishwasthoughtfromstudiesof PENNYCOOK (1998, 2001). In a global contextof neoliberal hegemony, identityissues are discussedbasedontheworkof RAJAGOPALAN (1998), MILTON SANTOS (2000), BAUMAN (2005), and MOITA LOPES (2008). The selected corpus for thisanalysisiscomposedoftwo series ofadvertisementsofaninstituteoflanguagesplaced in theStateof São Paulo (Brazil), gathered in websites. Resultsfromanalysissuggestthatcommercials are embedded in conflictingdialogicalrelationstiedtodiscursive, identity, andideologicalstreamsofcontemporaryglobalization, providingevaluativepositionsregardingthe status whichEnglishhastoday, andthesubjectsthislanguageinteractswith